The use of chitosan-coated flexible liposomes as a remarkable carrier to enhance the antitumor efficacy of 5-fluorouracil against colorectal cancer - Abdullah Alomrani; Mohamed Badran; Gamaleldin I. Harisa; Mohamed ALshehry; Moayed Alhariri; Aws Alshamsan; Musaed Alkholief (Elsevier, 2019)
Surface-coated nanocarriers have been extensively used to enhance the delivery of anticancer drugs and improve their therapeutic index. In this study, chitosan (CS)-coated flexible liposomes (chitosomes) containing 5-fluorouracil (5-FU) were designed and characterized for use as a novel approach to target colon cancer cells. 5-FU-loaded flexible liposomes (F1, F2, and F3) and 5-FU-loaded chitosomes (F4, F5, and F6) were prepared using film hydration and electrostatic deposition techniques, respectively. The particle size, polydispersity index (PDI), zeta potential, entrapment efficiency (EE%), morphology, and in vitro drug release ability, and cytotoxicity of the formulations were determined. The results revealed that the size of chitosomes ranged from 212 to 271 nm with a positive surface charge of 6.1 to 14.7 mV, whereas the particle size of liposomes ranged from 108 to 234 nm with negative surface charges of −2.3 to −16.3. F3 and F6 had a spherical shape with a rough surface structure. The in vitro drug release study revealed that chitosomes retard 5-FU release as opposed to the 5-FU solution and liposomes. The cytotoxicity study using a colon cancer cell line (HT-29) showed that 5-FU-loaded chitosomes were more effective in killing cancer cells in a sustained manner than liposomes and the 5-FU solution. Chitosomes were therefore successfully developed as nanocarriers of 5-FU, with potential cytotoxicity for colorectal cancer cells. Keywords: Liposomes, Chitosomes, 5-fluorouracil, Colorectal cancer